2001
DOI: 10.1007/bf03036717
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and breadmaking properties of wheat samples infected withFusarium spp.

Abstract: Rheological and breadmaking properties of untreated and suboptimally stored wheat samples (grain moisture: 20%, temperature: 20°C) and also of wheat which was inoculated withFusarium spp. were investigated. The deoxynivalenol (DON) content of the stored and inoculated wheat samples ranged between 820-12,000 μg/kg. Gluten proteins were isolated with different extraction solutions and the fractions obtained were analysed by means of RP-HPLC. Microextension tests and micro-baking tests were used for the determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…This indicates that Fusarium spp. infection may alter protein quality in grain, in accordance with findings of [6,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Content Of Mycotoxins and Standard Technological Quality Parsupporting
confidence: 83%
See 1 more Smart Citation
“…This indicates that Fusarium spp. infection may alter protein quality in grain, in accordance with findings of [6,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Content Of Mycotoxins and Standard Technological Quality Parsupporting
confidence: 83%
“…On the other hand, there are some contradictory studies where a strong Fusarium spp. contamination did not significantly influence the bread making properties [23,24]. Some authors mentioned an increase of protein content of the wheat grain after the Fusarium spp.…”
Section: Content Of Mycotoxins and Standard Technological Quality Parmentioning
confidence: 98%
“…inoculated variants. Our results are in correlation with conclusions of Antes et al (2001) who assessed Aspergillus and Penicillium species and concluded that fungal contamination have reduced dough resistance and extensibility influencing low bread volume. In contrary, Prange et al (2005) reported that that Fusarium infection did not negatively influence baking quality highlighting concerns that fungal contamination and their mycotoxins is not evidenced through baking quality analysis which might have considerable impact on food safety.…”
Section: Technological Quality Parameterssupporting
confidence: 90%
“…It is also not possible to expect a similar sensitivity as in concentrations of samples markedly overstepping hygienic limit could be explained by a higher activity of Fusarium infections which negatively affect the wheat grain properties. These changes can be readily recorded in NIR spectra and statistically evaluated (Antes et al 2001, Prange et al 2005. Improvement of DON prediction by FT-NIR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%